2019
DOI: 10.5120/ijca2019918514
|View full text |Cite
|
Sign up to set email alerts
|

POS Tagging of Gujarati Text using VITERBI and SVM

Abstract: Grammatical feature (POS) Labeling is a testing undertaking to distinguish the significance of each word in a sentence. This paper shows the assignment of distinguishing Grammatical form TAG for each transform in a Guajarati sentence utilizing the system of support Vector Machine and Viterbi deciphering method. Guajarati corpus of 1700 words is taken and tried it precisely. Labeling is done utilizing Viterbi and SVM and the outcome is examined in four classifications. In every one of the classifications Viterb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Using additional previous knowledge samples, support vector machines were employed to categorize stock forum postings [17]. Another research [18] has suggested the importance of machine learning in the ecommerce area and the use of cloud platforms for predictive analysis. The decision table was one of the top classifiers with high accuracy among the eleven data mining classification approaches studied [1].…”
Section: A Theories and Critical Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Using additional previous knowledge samples, support vector machines were employed to categorize stock forum postings [17]. Another research [18] has suggested the importance of machine learning in the ecommerce area and the use of cloud platforms for predictive analysis. The decision table was one of the top classifiers with high accuracy among the eleven data mining classification approaches studied [1].…”
Section: A Theories and Critical Reviewmentioning
confidence: 99%
“…It can choose and retrieve attributes automatically using the neural network structure and benefit from its own failures. [18] proposed that two predictive paradigms were built on real cloud platforms using popular machine learning classification algorithms: multi-class decision forest and multi-class logistic regression. The performance of both the models were evaluated on basis of classification accuracy on one percent data.…”
Section: B Gap Analysismentioning
confidence: 99%
See 3 more Smart Citations